Primary Prevention Program of Obesity among Primary School Children - Amina Mohamed Ismail; Hanaa Abdel Hakeem Ahmed; Frial Fouad Malika (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Childhood obesity is a serious medical condition that affects children and adolescents. It’sparticularly troubling because the extra pounds often start children on the path to health problems thatwere once considered adult problems: diabetes, high blood pressure and high cholesterol. Aim of theStudy: assess the effect of primary prevention program of obesity among primary school children through:assessing knowledge & practices of primary school children related to obesity, Designing, implementingprimary prevention program of obesity among primary school children, evaluating the effectiveness ofprimary prevention program on knowledge & practices related to obesity among primary school children.Subjects and Methods: Setting: The study was conducted in four primary governmental school of El-Salamcity , Cairo governorate including: (El Hussien, Osman Ben Afan, Atef El Sadat and Gamal Abdel Naser).Size: the sample composed of 144 primary school children chosen randomly through multistage sampling .Tools: Different tools were used for data collection of study and it was written in simple language to suit theunderstanding level of the studied primary school children First tool: Structured interviewing questionnaire,second tool: Anthropometric Measurements , physical assessment sheet Results: clarified that only fewpercentage of primary school children had good Knowledge preprogram while this improved to more thanone third post program implementation related to their total knowledge about childhood obesity , there washighly statistically significant difference in post-program compared to pre-program according to their totalpractice related to childhood obesity. Conclusions: primary school children improved their knowledge andpractice regarding childhood obesity after program implementation. Recommendation: primary preventionprogram must be provided for all primary school children to prevent childhood obesity risks.